Competition, non-financial measures and the effectiveness of management control systems - Ibrahim, Mohd Yussoff; Ibrahim, Daing Nasir; Sanda, Ahmadu Umaru (Universiti Utara Malaysia, 2001)
This paper reports the results of an empirical study examining the relationship between the emphasis on non-financial measures and two other variables; the intensity of competition and the effectiveness of a management control system, in a manufacturing company. Two important issues focused in the study are: does competition compel managers to utilize more nonfinancial measures in decision making and is the emphasis given to nonfinancial measures worthwhile? Data from 105 manufacturing companies throughout Malaysia were analyzed using correlation and regression analysis. The results of both analyses indicate that the emphasis given to nonfinancial measures in decision making has a positive correlation with the effectiveness of a management control system and secondly, the intensity of competition faced by an organization is positively correlated with the emphasis on non-financial indicators. Descriptive analysis was also performed to evaluate the distribution of emphasis on non-financial measures by the age, location, ownership, size of an organization and its industry.